Biodiversity and Spatial-Temporal Dynamics of Margalefidinium Species in Jiaozhou Bay, China - Shuya Liu (MDPI AG, 2021)
Many Margalefidinium species are cosmopolitan harmful algal bloom (HAB) species that have caused huge economic and ecological damage. Despite extensive research on Margalefidinium species, the biodiversity and spatial-temporal dynamics of these species remain obscure. Jiaozhou Bay is an ideal area for HAB research, being one of the earliest marine survey areas in China. In this study, we carried out the first metabarcoding study on the temporal and spatial dynamics of Margalefidinium species using the 18S rDNA V4 region as the molecular marker and samples collected monthly at 12 sampling sites in Jiaozhou Bay in 2019. Two harmful Margalefidinium species (M. polykrikoides and M. fulvescens) were identified with potentially high genetic diversity (although we cannot rule out the possibility of intra-genome sequence variations). Both M. polykrikoides and M. fulvescens demonstrated strong temporal preference with a sharp peak of abundance in early autumn (September), but without showing strong location preference in Jiaozhou Bay. Our results revealed that temperature might be the main driver for their temporal dynamics. Knowledge of biodiversity and spatial-temporal dynamics of the Margalefidinium species may shed light on the understanding of mechanisms underlying strongly biased occurrences of Margalefidinium blooms recorded globally.